Declined circulating Elabela levels in patients with essential hypertension and its association with impaired vascular function: A preliminary study. (2nd April 2020) - Li, Yutao; Yang, Xulong; Ouyang, Shun; He, Jiang; Yu, Bingbo; Lin, Xiufang; Zhang, Qunying; Tao, Jun
ABSTRACT: Background : Elabela (ELA) is a newly identified endogenous ligand of apelin receptor (APJ) which has been confirmed to be implicated in the pathogenesis of hypertension. Previous experiments have revealed the critical role of ELA in eliciting vasodilation and lowering blood pressure. However, the role of plasma ELA levels in hypertensive patients and its relationship with vascular function have not been investigated. Method : Thirty-one patients with essential hypertension (EH) and 31 age-matched healthy subjects as controls were recruited in the study. Plasma ELA concentration and vascular function parameters including brachial artery flow-mediated dilation (FMD) and brachial–ankle pulse wave velocity (baPWV) were measured. Results : We observed remarkably lower plasma ELA concentration in hypertensive patients as compared with controls (1.29 ± 0.56 ng/ml vs. 1.79 ± 0.55 ng/ml; P = 0.001). Linear correlation analysis showed that ELA was negatively correlated with systolic blood pressure ( r = −0.388, P = 0.002) and diastolic blood pressure ( r = −0.321, P = 0.011) and positively correlated with FMD ( r = 0.319, P = 0.011). There was no statistically significant relationship between ELA and baPWV ( r = 0.234, P = 0.067). Stepwise multiple linear analysis also identified a close association of plasma ELA levels with endothelial function. Conclusion : The present study demonstrates for the first time that circulating ELA levels are reduced in patients with EH. The fall in endogenous ELA levels may be involved in the pathogenesis of hypertension-related vascular damage.